Pengaruh Penggunaan Komik Berbasis Android Dalam Edukasi Tentang Sayur dan Buah Terhadap Pengetahuan dan Sikap Anak Usia Sekolah Dasar Kelas 4 dan 5 di Desa Tlogo Kabupaten Blitar - Samsiana, Danti Latifah; Sulandjari, Siti (Jurnal Gizi dan Kesehatan Nusantara, 2023)
AbstractAndroid-based comics are a series of sequential picture stories that convey information that can be accessed using Android. Comics are part of the educational media that can be used to increase mastery of knowledge and attitudes about vegetables and fruit in elementary school children. The purpose of this study was to determine the effect of using android-based comics as a media for nutrition education on mastery of knowledge and attitudes about vegetables and fruit in elementary school-aged children in grades 4 and 5 in Tlogo Village, Blitar Regency. The type of research is quasi-experimental, using a two group pretest posttest design where there are 2 groups, namely the experimental group using android-based comic education media and the control group using leaflet educational media. The subjects of the study were 64 elementary school aged children in grades 4 and 5. 32 children were taken as samples from the experimental group and 32 children from the control group. The independent variable in this study was the use of android-based comic educational media, while the dependent variable was knowledge as measured using a test, and attitudes about vegetables and fruit as measured using a questionnaire. Statistical analysis was performed using the t test with a significant level of p ? 0.05. The results in this study showed that nutrition education using comic education media based on Android had an effect on mastery of knowledge (p = 0.003) but had no effect on attitudes (p = 0.263) in elementary school children in grades 4 and 5 in Tlogo Village, Blitar Regency.